Penegakan Hukum Pidana terhadap Korporasi dalam Tindak Pidana Korupsi - Sachruddin Sachruddin; Yusrianto Kadir; Marten Bunga (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Eradication of corruption in Indonesia has been made maximum efforts, but the reality shows that the number of corruption cases continues to increase. This situation is caused by the obstacles encountered in efforts to prevent and eradicate corruption. In its development, corruption in Indonesia is no longer a monopoly of bureaucrats but has also involved actors in the private sector. For example, corruption can be committed by corporations, either directly or through the actions of people acting on behalf of or for the interests of the corporation. The method used is the normative juridical method, a legal research method that relies on the study of primary legal materials, such as laws, legal theories, and legal concepts. This method is analytical and examines the legal norms applicable in laws and regulations. Enforcement of criminal law against corporations in corruption cases is an important aspect in efforts to eradicate corruption in Indonesia. Corporations are responsible for actions taken in their interests. Sanctions imposed on corporations, either in the form of fines or administrative sanctions, are expected to provide a deterrent effect and prevent the recurrence of corruption. Criminal law enforcement against corporations in corruption cases faces various complex and diverse obstacles. These obstacles include the complexity of the corporate organizational structure, difficulty in providing evidence, transfer of responsibility, lack of clear regulations, minimal sanctions imposed.